A new endemic Impatiens species on Mount Gorongosa (Mozambique) demonstrates the conservation importance of montane areas in Africa - Janssens, Steven B.; Ballings, Petra; Mertens, Arne; Dessein, Steven (Phytotaxa, 2018)
A new Impatiens species from Mozambique, Impatiens wuerstenii, is described and illustrated. The material used for the description was initially mistaken for the morphologically similar Impatiens species I. psychadelphoides, a known endemic from Mozambique. However, a combined molecular – morphological study demonstrates that the populations found on Mount Gorongosa do not belong to I. psychadelphoides but are a species on their own. Phylogenetic analyses based on chloroplast and nuclear gene markers demonstrate that I. wuerstenii is sister to the floral morphologically distinct I. salpinx, and that I. psychadelphoides and I. cecilii are sister to that lineage. The presence of a new endemic species on Mount Gorongosa indicates the importance of this mountain area on the overall biodiversity of the region and emphasizes the need for a more thorough conservation and biological exploration of the mountain.